Pengaruh Penggunaan Gadget Terhadap Perkembangan Anak: Studi Kasus di Sekolah Dasar - Rahmawati, Nadia; Dapit Aryando; Syaffrizal Aziz; Sani Safitri; Syariffudin (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
The use of gadgets in children's lives, especially elementary school students, has increased with technological advancements. This study aims to analyze the influence of gadgets on the development of elementary school children in cognitive, social, emotional, and physical aspects. The research method used is a literature review, collecting various related studies to explore both positive and negative impacts of gadget use. The results show that gadgets can enhance information access and support learning if used wisely. However, excessive use can lead to reduced social interaction, concentration disorders, and various physical and emotional health issues. Therefore, it is crucial for parents and educators to regulate and guide gadget usage so that children can benefit from technology without experiencing its negative effects. This study provides new insights into the importance of gadget usage regulation in children's daily lives to support balanced development.